Bony Orbital Decompression in Patients with High Myopia and Pseudoexophthalmos - Daser, Anke; Mattheis, Stefan; Stähr, Kerstin; Lang, Stephan; Bechrakis, Nikolaos E.; Dekowski, Dirk; Eckstein, Anja (Klinische Monatsblätter für Augenheilkunde, 2020)
Introduction High myopic eyes grow in length (> 0.35 mm/dpt) more than in height and width leading to a disturbing unilateral exophthalmos in patients with anisomyopia and – more rarely – a bilateral exophthalmos in high myopia affecting both eyes. Secondary consequences are sicca symptoms and painful eye mobility due to a large bulbus in a too small bony orbit. The aim of the work was to evaluate the effectiveness of bony orbital compression in cases of high myopia.Material and Methods Four patients underwent bony orbital decompression between the years 2012 and 2019. Two of the patients received lateral and two of them balanced (medial endonasal endoscopic and lateral) decompression. The decompression effect, complications and the influence of decompression on eye position and motility were evaluated.Results Significant decompression effect was achieved in all patients. As a result, symmetry was restored in all unilaterally affected patients. No complications occurred. The lateral decompression had a positive effect on the preexisting convergent strabismus (reduction of the “eso” position, neutral to the vertical deviation). The carefully dosed medial decompression did not lead to any change of the horizontal position in one patient and in the other exotropic patient it resulted in a 10 pdpt of “exo” reduction without developing an “eso” position.Discussion The bony orbital decompression provides a sufficient decompression effect in the four patients to reduce the myopic pseudoexophthalmos. The alignment anomalies associated with a high myopia (“heavy eye”) was favourably influenced by the lateral decompression.Hintergrund Die hohe Myopie ist wesentlich durch eine Verlängerung des Bulbus (0,35 mm/dpt) – und weniger durch dessen Höhen- oder Breitenzunahme – charakterisiert. Dies kann vor allem bei einer Anisomyopie zu einem störenden einseitigen Pseudoexophthalmus führen, in selteneren Fällen einer beidseitigen hohen Myopie auch zu einem störenden beidseitigen Pseudoexophthalmus. Sekundärfolgen können Sicca-Symptome sowie Schmerzen bei der Augenbewegung durch einen großen Bulbus in einer zu kleinen knöchernen Orbita sein. Ziel der Arbeit war es, die Wirksamkeit einer knöchernen Orbitadekompression bei hoher Myopie zu analysieren.Patienten und Methoden Vier Patienten unterzogen sich in der Zeit zwischen 2012 und 2019 einer knöchernen Orbitadekompression. Zwei Patienten erhielten eine laterale Dekompression und 2 Patienten eine balancierte (mediale und laterale) Orbitadekompression. Ausgewertet wurden: Exophthalmusreduktion, Komplikationen und Einfluss der Dekompression auf Augenstellung und Beweglichkeit.Ergebnisse Die Operation führte bei allen Patienten zu einem signifikanten Proptosisrückgang (3 – 5 mm). Bei Patienten mit einseitiger Erkrankung konnte eine Symmetrie zum gesunden Auge hergestellt werden. Die laterale Dekompression allein wirkte sich günstig auf die vorbestehende Schielstellung aus (Verringerung der „Eso“-Stellung, neutral zu Vertikaldeviation). Die vorsichtig dosierte mediale Dekompression führte bei einem Patienten zu keiner Änderung der horizontalen Augenstellung und bei dem anderen exotropen Patienten zu 10 pdpt „Exo“-Reduktion ohne Umschlag in eine „Eso“-Stellung.Schlussfolgerung Die knöcherne Orbitadekompression leistete bei den 4 Patienten eine suffiziente Proptosisreduktion des myopen Pseudoexophthalmus. Mit einer hohen Myopie auftretende „Eso“-Stellungsanomalien wurden durch die laterale Dekompression günstig beeinflusst.
Keywords: orbital decompression; orbit; exophthalmos; high myopia